Voluntary markets for carbon offsets: Evolution and lessons for the LNG market - A. Bose; Jeff Cohen; Bassam Fattouh; O. Johnson; G. Spilker (The Oxford Institute for Energy Studies, 2021)
National commitments to cut greenhouse gas (GHG) emissions currently fall far short of what is needed to meet the goal of the 2015 Paris Agreement to limit global warming to 1.50 C and no more than 20 C. Meeting this goal will require an estimated 45% reduction in global emissions by 2030, reaching net-zero emissions by 2050 with a continuing decline beyond that date. In response to this imperative, companies in every economic sector, along with national and regional governments, cities, universities, and investors are making their own commitments to reach net-zero emissions. Of the 1,500 companies that have made net-zero commitments, it can be assumed that a substantial number are considering purchase of carbon offsets for at least some portion of their emission reduction targets. This is consistent with the surge in demand for voluntary carbon offsets. Since the first carbon offset project in 1989, global markets for carbon offsets have become valued at more than 5 billion annually, doubling each year since 2018, and are projected to increase by as much as a factor of 15 or more by 2030 as companies and countries set ambitious goals for net-zero CO2 emissions. In parallel, carbon offsets are attracting elevated scrutiny for their role in meeting climate goals. While there has been considerable progress in establishing standards for rigorous monitoring, verification and reporting protocols, there has also been a legitimate debate regarding the role and efficacy of offsets in meeting science-based targets. For example, offsets have been criticized as not consistently delivering climate and other environmental benefits, or as providing a relatively cheap way for companies to meet "net-zero" goals, substituting for, and possibly disincentivizing core investments in operational efficiencies, renewable energy, technology innovations, or procurement of low-carbon inputs into supply chains. This paper provides an overview of key trends in carbon offset markets along with recommendations for buyers and sellers on how to participate effectively in an evolving market landscape. The focus here is on the development of exchanges and spot and futures contracts tradable on these marketplaces to generate reliable price signals and liquidity, drawing on examples from the LNG industry. While 'bundling' LNG cargoes or other commodity transactions with carbon offsets can be relatively straightforward via exchanges and spot and futures contracts, the use of carbon offsets in these types of commodity transactions are attracting elevated scrutiny regarding their contribution to meeting climate change targets.
Keywords: 330; Carbon Neutral LNG; Carbon offsets; Climate Change; Energy Transition; LNG; Net Zero Emissions; Voluntary Carbon Markets